1999
DOI: 10.1063/1.123192
|View full text |Cite
|
Sign up to set email alerts
|

Modal expansion analysis of strained photonic lattices based on vertical cavity surface emitting laser arrays

Abstract: The optical modes of lasing photonic lattices incorporating alternating-shear strain were analyzed using a background-resonator mode expansion model. The model correctly explains the observed locking of the photon mode near fields to square or hexagonal-like lattice patterns for subcritical strain values, as well as the abrupt switching between the two mode patterns. Control of the optical mode switching point by adjusting the lattice reflectivity is proposed and analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The analytical tools used for diffractive coupling are similar to the very early work on laser resonator modes resulting from the formulation of Fox and Li (1961). In this case, the analysis demands that a resonator mode be a field distribution that repeats itself after one round trip through the cavity, up to a multiplicative factor: FIGURE 6.7 Illustration of field sharing between neighboring sources via diffraction and patterned reflectivity.…”
Section: Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical tools used for diffractive coupling are similar to the very early work on laser resonator modes resulting from the formulation of Fox and Li (1961). In this case, the analysis demands that a resonator mode be a field distribution that repeats itself after one round trip through the cavity, up to a multiplicative factor: FIGURE 6.7 Illustration of field sharing between neighboring sources via diffraction and patterned reflectivity.…”
Section: Principlesmentioning
confidence: 99%
“…For that reason, other formulations of the diffractively coupled array analysis have been developed (Fishman et al, 1997(Fishman et al, , 1999(Fishman et al, , 2001Hardy et al, 1998). In actuality, the coupling occurs between Coherent Coupling of Vertical-Cavity Surface-Emitting Laser Arrays multiple modes of the different resonators, which greatly increases the complexity of the problem.…”
Section: Principlesmentioning
confidence: 99%
“…2,3 Several models allow more precise calculations of the fundamental transverse mode. [6][7][8] The MOVPE grown, top emitting arrays under study are designed for emission at ϭ960 nm. The 1-Al 0.15 Ga 0.85 As cavity with three InGaAs quantum wells is followed on the p side by a /2-layer containing a 25 nm thick AlAs oxidation layer at the minimum of the optical field.…”
Section: Continuous-wave Operation Of Phase-coupled Vertical-cavity Smentioning
confidence: 99%
“…[1][2][3] One particular example of such 2D structures is the photonic resonator lattice based on arrays of coupled vertical cavity surface emitting lasers ͑VCSELs͒. [4][5][6][7][8] In this case, a photonic band of lateral photon modes is formed due to the coupling between individual VCSELs in the array. A particularly convenient way for realizing these lattices is using metallic patterning of the top Bragg mirror of a VCSEL wafer.…”
mentioning
confidence: 99%
“…[5][6][7] In particular, the evolution of the lasing mode in an alternating shear strained structure ͑i.e., laterally shifted lattice͒ was investigated as the lattice structure evolved from a square array to a quasihexagonal one. It was demonstrated that rather than following the modification in the underlying lattice, the lasing photon mode switches abruptly between the mode of the square lattice and that of the quasihexagonal one at a critical strain value.…”
mentioning
confidence: 99%